0300 Linking Sleep Disturbances with Amyloid and Tau Imaging. Preliminary Findings from the Harvard Aging Brain Study. (12th April 2019) - Djonlagic, Ina; Chhatwal, Jasmeer; Schulz, Aaron; Hampton, Olivia; Kirn, Dylan; Papp, Kathryn; Rentz, Dorene; Johnson, Keith; Sperling, Reisa; Redline, Susan
Abstract: Introduction: Growing evidence suggests that sleep disturbances can modulate the aging process and increase the risk of developing cognitive impairment and dementia. Given that sleep and cognition share biological regulatory mechanisms, the aim of this study was to characterize the association between sleep disturbances and imaging markers of Alzheimer's disease (amyloid and Tau) in participants of the Harvard Aging Brain Study in relation to their cognitive status. Methods: We carried out home level 2 polysomnography studies on 24 participants of the prospective Harvard Aging Brain Study. As part of this longitudinal study, individuals, who were recruited when cognitively intact, undergo longitudinal multi-modality imaging including Pittsburgh Compound B PET scans to detect amyloid deposition and Tau imaging using the F18-labeled ligand (T807) as well as sensitive yearly cognitive assessments, including the Preclinical Alzheimer's Cognitive Composite (PACC), to define predictive factors of preclinical Alzheimer's disease. Results: Among the participants, 14 were female and the average age was 74.1 (±1.97). A positive correlation was found between inferior temporal Tau and percent time in N1 sleep (p=0.006), whereas percent time in N3 (slow-wave) sleep (p=0.016) and REM sleep (p = 0.05) were inversely and independently correlated with inferior temporal Tau. Cortical amyloid burden correlated positively with percent time in N1 (p=0.01). All these associations remained after controlling for age and total sleep time. PACC score correlated positively with percent time in N1 (p= 0.04) and negatively with REM sleep (p = 0.001) although this association diminished after correction for age and total sleep time. We did not find any associations between measures of sleep disordered breathing and amyloid or Tau. Conclusion: Our preliminary findings provide evidence for a relationship between specific measures of sleep architecture and PET signals from amyloid and Tau tracers. Sleep disturbances thereby have a potential to serve as surrogate markers for cognitive decline, could help to predict high-risk individuals and offer new approaches for therapeutic targets. Support (If Any): AASM Foundation Bridge to Success Award (PI: Djonlagic)